The Character of Maritime Nation In Facing The Global Challenge: A Historical Perspective - Zuhdi, Susanto (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The distinctive mark of maritime nation is the greatness in sailing and building the maritime civilization. The creativity and innovative through the perseverance, are the attached characters in the behavior of maritime nation. From the track record, the people who live in this archipelago have shown their ability as maritime nation in opening the new rooms for life that have global nature and developing the maritime culture. The globalization in history of civilization occurred in the regions which connected by the peoples of Austronesia/Malay/Indonesia through the ocean. The exploration ability lies on this archipelago. A lot of people count on their life on the sea. The character components of nation maritime in this Archipelago are indicated with the openness, tolerant, and adaptive in accepting and responding the global challenge. The numerous metaphors of archipelago people relates with the sea. The strong maritime nation should also be able to build the great maritime state.